Potential Triazole-based Molecules for the Treatment of Neglected Diseases - Mantoani, Susimaire P.; de Andrade, Peterson; Chierrito, Talita P. C.; Figueredo, Andreza Silva; Carvalho, Ivone (Current Medicinal Chemistry, 2019)
Neglected Diseases (NDs) affect million of people, especially the poorest population around the world. Several efforts to an effective treatment have proved insufficient at the moment. In this context, triazole derivatives have shown great relevance in medicinal chemistry due to a wide range of biological activities. This review aims to describe some of the most relevant and recent research focused on 1,2,3- and 1,2,4-triazolebased molecules targeting four expressive NDs: Chagas disease, Malaria, Tuberculosis and Leishmaniasis.
Keywords: chagas disease